Uganda Industrial Research Institute : Uganda Case Study - World Bank (Washington, DC, 2014)
The Uganda industrial research institute (UIRI), a traditional incubator run by the government, has made a significant impact by locating value-added processing systems from its Kampala headquarters into farmer communities. While the model lacks the necessary innovation development, UIRI offers small and medium enterprise (SME) clients in these regions the opportunity to expand personal income and existing businesses through local market development and value-added food processing. At the same time, however, UIRI's traditional incubator has been challenged to graduate incubatees who do not have the financial resources to stand on their own. UIRI has revised its mandate, purpose, and organizational structure to better address its mission and the country s industrial development strategies. This has resulted in a more dynamic, flexible, and responsive organization geared towards: (a) technology development and transfer; (b) business development services; (c) industrial services; (d) pilot plants and prototyping; and (e) UIRI millennium science initiative (MSI).